2012
DOI: 10.3109/08820538.2012.708812
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-wide Field Retinal Imaging in Detection, Classification, and Management of Diabetic Retinopathy

Abstract: Current ultra-wide field (UWF) retinal imaging systems utilize scanning laser ophthalmoscope technology combined with an ellipsoidal mirror to capture up to 200 degrees of the retina in a single image. When compared with mydriatic ETDRS-protocol, 7 standard field photographs and clinical examination, nonmydriatic UWF images appear to have excellent agreement in allowing the detection and classification of diabetic retinopathy (DR), although larger, definitive validation studies are still forthcoming. UWF imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 46 publications
0
36
1
Order By: Relevance
“…Although the Optomap has been shown to have an improved ability to image peripheral pathology compared to the ETDRS 7-standard field imaging in diabetic retinopathy, [1][2][3] and it also has a higher capability to image peripheral CMV retinitis lesions than conventional photography, 14 UWF still may fail to expose lesions that are in the far peripheral retina, such as the case with retinal hole and tears. Mackenzie et al found that detection of lesions posterior to the equator had a 74% sensitivity, while detection of lesions anterior to the equator was much lower with a 45% sensitivity.…”
Section: Discussionmentioning
confidence: 93%
“…Although the Optomap has been shown to have an improved ability to image peripheral pathology compared to the ETDRS 7-standard field imaging in diabetic retinopathy, [1][2][3] and it also has a higher capability to image peripheral CMV retinitis lesions than conventional photography, 14 UWF still may fail to expose lesions that are in the far peripheral retina, such as the case with retinal hole and tears. Mackenzie et al found that detection of lesions posterior to the equator had a 74% sensitivity, while detection of lesions anterior to the equator was much lower with a 45% sensitivity.…”
Section: Discussionmentioning
confidence: 93%
“…The term ‘widefield’ (WF) has been used by several authors to describe SD-OCT imaging of the retina within a 50 o field of view, while ultra-widefield (UWF) has been reserved for the description of capturing 200 o field of view in a single image. 8-11 While en-face UWF-based fundus autofluorescence and fluorescein angiography imaging have illuminated our understanding of the pathological features of the peripheral retina in vascular diseases such as non-perfusion in diabetic retinopathy, 12 cross-sectional anatomic information generally remains absent.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that significant retinopathy can be found outside the posterior pole, and in many of these patients, the peripheral findings would suggest a higher level of DR severity than if only the posterior pole were considered (Soliman et al. ; Wessel et al. ; Silva et al.…”
Section: Introductionmentioning
confidence: 99%
“…These pseudocolour images (acquired by combining red and green scanning lasers) appear to be adequate for detecting DR lesions. Recent studies have shown that significant retinopathy can be found outside the posterior pole, and in many of these patients, the peripheral findings would suggest a higher level of DR severity than if only the posterior pole were considered (Soliman et al 2012;Wessel et al 2012;Silva et al 2013Silva et al , 2015b. Moreover, eyes with predominantly peripheral disease have a 4.7-fold higher risk of progression to proliferative diabetic retinopathy (PDR) at 4 years (Silva et al 2015a).…”
Section: Introductionmentioning
confidence: 99%